Water Use and Water Productivity of Agroforestry Systems in the Semi-arid Tropics - Ong, C K; Anyango, S; Muthuri, C W; Black, C R (Annals of Arid Zone, 2016)
The greatest challenge for agroforestry in dryland areas is to identify species combinations and management systems which optimize the capture of scarce available water supplies and minimize the inevitable competition between trees and crops. This review describes recent advances in research concerning water use and tree-crop interactions in the semi-arid tropics, focusing on studies in India and Africa, where farming systems involving the incorporation of trees with crops are becoming increasingly popular. We begin by establishing why and how farmers practice agroforestry in dryland areas in order to identify the rationale underlying their decisions and the tree management practices employed and to provide a starting point for developing future options; only a limited number of tree species are preferred by farmers in semi-arid areas of Kenya and elsewhere in East Africa. We explore how agroforestry may enhance rainfall utilization by improving temporal and spatial complementarity in resource capture. A key, but simple, identifiable trait is the leafing phenology of the tree species involved as this may be used to assess their suitability for effective water management in agroforestry systems. The feasibility of root pruning to reduce competition for water and optimization of the benefits of microclimatic modifications in agroforestry systems is also considered. Finally, we consider how agroforestry may be used to cope with predicted climate change, which is expected to affect subsistence farmers most severely in the semi-arid tropics. Key words: Climate change. hydraulic lift, tree-crop interactions. phenology. water use.